Education and social economic training - Lucio-Paredes, Alex (2022)
In recent decades, official discourses have attributed to education the power to solve all social phenomena that threaten and undermine life. This paper aims to specify and provide elements that allow an understanding of the relationship between education and society. Based on the concepts of education and social economic formation, our objective is to describe the relationship between: 1) education and economic infrastructure; 2) education and juridical-political superstructure; and 3) education and ideological superstructure. The study is theoretical in nature. The philosophical perspective used comes from the postulates of historical materialism and critical pedagogy. The methodology applied is based on the main guidelines of the qualitative approach, with a descriptive level of depth. The bibliographic method was used, as well as the techniques of text analysis, summaries and conceptual schemes. In the conclusions, it is exposed that the described relations allow: 1) to accelerate the qualification of the labor force; 2) to guarantee the respect for the division of labor and, to naturalize exploitation as a form of relation between human beings; 3) to create the political-legal conditions for the reproduction of the mode of production, through the joint action of the State-right-education; 4) to consolidate the ideological hegemony of the dominant social class, through the school and the official curriculum.